Incretin-based approaches for type 2 diabetes therapy: effects on circulating cytokines and adipocyte’s secretome - Margarita Agareva; Svetlana Michurina; Alina Tomilova; Ekaterina Shestakova; Anastasia Voznesenskaya; Maria Sineokaya; Ekaterina Zubkova; Elizaveta Ratner; Iurii Stafeev; Yelena Parfyonova; Marina Shestakova (BMC Endocrine Disorders)
Abstract Background Adipose tissue secretome plays a crucial role in the mechanisms of metabolic diseases. Weight loss has a favourable effect on the adipose tissue secretome and prevents the development of type 2 diabetes mellitus (T2DM) and its complications. The most effective methods of glycaemic control are bariatric surgery (BS) and pharmacotherapy. The aim of our study is to evaluate changes in adipose tissue secretome after BS and semaglutide injections. Methods 17 patients with T2DM were examined before and 6 months after BS or semaglutide therapy. The examination protocol included anthropometry, clinical biochemistry, insulin resistance evaluation and collection of subcutaneous adipose tissue biopsies. Adipose derived stem cells (ADSC) were isolated from biopsies according to a standard enzymatic protocol and differentiated into white and beige adipocytes. Adipogenesis and thermogenesis were assessed by confocal microscopy. Secretome of adipocytes and cytokines plasma levels were analyzed using a MILLIPLEX panel. Results Following BS and semaglutide therapy, a decline in BMI, total fat content, HbA1c, and fasting blood glucose was observed. Insulin sensitivity increased only 6 months after BS. Semaglutide therapy resulted in the elevation of angiogenic and proinflammatory cytokines in adipocyte secretory profile. After BS we also detected the increase in proinflammatory cytokines both in adipocyte secretome and in plasma levels. However, the adipocyte secretome subsequent to bariatric surgery (BS) exhibited a reduced proinflammatory response in comparison to that observed following semaglutide therapy. Conclusions The effect of semaglutide injections directly on adipose tissue can change the function of ADSC, making them more angiogenic and adipogenic. A decrease in BMI, HbA1c and insulin resistance is achieved to a significant extent only after BS. BS-induced T2DM remission is related to lower pro-inflammatory secretion from adipocytes as compared to semaglutide. The regulation of inflammation in adipocytes may serve as a potential mechanism underlying BS-induced T2DM remission.